Gait Characteristics in a Canine Model of X-linked Myotubular Myopathy - Goddard, Melissa A. (J Neurol Sci, 2014)
X-linked myotubular myopathy (XLMTM) is a fatal pediatric disease where affected boys display profound weakness of the skeletal muscles. Possible therapies are under development but robust outcome measures in animal models are required for effective translation to human patients. We established a naturally-occuring canine model, where XLMTM dogs display clinical symptoms similar to those observed in humans. The aim of this study was to determine potential endpoints for the assessment of future treatments in this model. Video-based gait analysis was selected, as it is a well-established method of assessing limb function in neuromuscular disease and measures have been correlated to patient quality of life. XLMTM dogs (N=3) and their true littermate wild type controls (N=3) were assessed at 4–5 time points, beginning at 10 weeks and continuing through 17 weeks. Motion capture and an instrumented carpet were used separately to evaluate spatiotemporal and kinematic changes over time. XLMTM dogs walk more slowly and with shorter stride lengths than wild type dogs, and these differences became greater over time. However, there was no clear difference in angular measures between affected and unaffected dogs. These data demonstrate that spatiotemporal parameters capture functional changes in gait in an XLMTM canine model and support their utility in future therapeutic trials.